3-D conjugate heat transfer analysis of PLCC packages mounted in-line on a Printed Circuit Board - Yusoff, S.; Mohamed, M.; Ahmad, K.A.; Abdullah, M.Z.; Mujeebu, M.A.; Mohd Ali, Z.; Idrus, F.; Yaakob, Y. (2009)
This paper presents a three dimensional heat and fluid flow analysis of two Plastic Leaded Chip Carrier (PLCC) packages mounted in tandem arrangement on a Printed Circuit Board (PCB) exposed to the free stream velocity. The numerical simulation was done using FLUENT 6.3 and the experiments were performed by using an air chamber with nozzle, at different approach air velocities to emulate the forced convection heat transfer phenomena. Parameters such as junction temperature, thermal resistance and top surface average Nusselt number have been studied for each package by varying the chip power, spacing between the packages and approach air velocities. The decrease in the junction temperature of the packages with the increase in approach air velocity is clearly observed. Furthermore, the Nusselt number of PLCC 1 is always slightly higher than PLCC 2 for all approach velocities considered. The results also show that the spacing between packages influences the thermal resistance and average Nusselt number for both packages at a particular approach air velocity. The simulation results obtained are found in satisfactory agreement with the experimental results.